Urgency Living Values Education at Kindergarten Tiara Chandra Yogyakarta - Jamuna Ulfah; Suyadi Suyadi (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
The sides proper application of the methods in encouraging child blossoms and implanting character values becomes the primary focus of all early childhood education. Many of the methods and models offered to be used and referral in meeting these requirements. Living Values Education has become one of the methods that are present among communities to implant values focused on the character of learners. Those values are flexible, tailored to need, culture, and tradition. Hence researchers research at the Tiara Chandra Kindergarten Yogyakarta to understand the turmoil of the Living Values Education implementation on all the elements in that agency. The study uses a qualitative method of phenomenon ology, a small sample interview technique with data analysis of interpretive phenomena. Tiara Chandra Kindergarten Yogyakarta became one of the kindergartens in Yogyakarta that applied Living Values Education and integrated into the curriculum with twelve basic values of love, peace, cooperation, tolerance, sincerity, compassion, respect, honesty, humility, happiness, and unity. I create a peaceful atmosphere full of the rules, order, and peace contained in the setting of the values of a life lived with a smile. This creation is the essence of the association of Living Values Education in the Tiara Chandra Kindergarten Yogyakarta. Which can only happen if there is a cooperation between all sides. Keywords: Living Values Education; Kindergarten; Urgency. Abstrak Penerapan metode yang tepat dalam menstimulus tumbuh kembang anak serta penanaman nilai-nilai karakter menjadi fokus utama dari seluruh pendidikan anak usia dini. Banyak metode dan model yang ditawarkan untuk dapat digunakan dan dijadikan acuan dalam memenuhi tuntutan tersebut. LVE (Living Values Education) menjadi salah satu metode yang hadir di tengah-tengah masyarakat dengan tujuan penanaman nilai-nilai yang difokuskan kepada karakter peserta didik. Nilai-nilai tersebut bersifat fleksibel yang disesuaikan dengan keperluan, adat, budaya dan tradisi. Maka dari itu peneliti melaksanakan penelitian di TK Tiara Chandra Yogyakarta untuk mengetahui urgensitas dari implementasi LVE pada semua elemen di lembaga itu. Penelitian ini menggunakan metode kualitatif fenomenologi, teknik wawancara sampel kecil dengan analisis data berupa analisis fenomenologi interpretatif. TK Tiara Chandra menjadi salah satu TK yang ada di Yogyakarta yang menerapkan LVE dan diintegrasikan ke dalam kurikulum dengan 12 nilai dasar yaitu cinta, damai, kerjasama, toleransi, ikhlas, kasih sayang, tanggung jawab, penghargaan, kejujuran, kerendahan hati, kebahagiaan dan persatuan. LVE menciptakan nuansa damai yang penuh dengan aturan, keteraturan, dan kedamaian yang di muat dalam tatanan nilai-nilai kehidupan yang dijalankan dengan senyuman. Penciptaan ini merupakan makna atas urgensitas dari LVE di TK Tiara Chandra Yogyakarta. Yang mana semua hanya dapat terjadi jika ada kerjasama antar semua pihak. Kata Kunci: Living Values Education; Taman Kanak-Kanak; Urgensitas.